Disaggregating Asian American Cigarette and Alternative Tobacco Product Use: Results from the National Health Interview Survey (NHIS) 2006–2018 - Rao, Manaeha; Bar, Lilly; Yu, Yunnan; Srinivasan, Malathi; Mukherjea, Arnab; Li, Jiang; Chung, Sukyung; Venkatraman, Siddharth; Dan, Shozen; Palaniappan, Latha (Journal of Racial and Ethnic Health Disparities, 2022)
Introduction Asian Americans suffer high rates of smoking and tobacco-related deaths, varying by ethnic group. Trends of cigarette and alternative tobacco product use among Asian Americans, specifically considering ethnic group, sex, and nativity, are infrequently reported. Methods Using National Health Interview Survey (NHIS) data from 2006–2018 and the 2016–2018 alternative tobacco supplement (e-cigarettes, cigars, smokeless tobacco, pipes), we explored cigarette and alternative tobacco product use by Asian ethnic group (Asian Indian ( n = 4373), Chinese ( n = 4736), Filipino ( n = 4912)) in comparison to non-Hispanic Whites (NHWs ( n = 275,025)), adjusting for socioeconomic and demographic factors. Results Among 289,046 adults, 12% of Filipinos were current smokers, twice the prevalence in Asian Indians and Chinese ( p < 0.001). The male–female gender difference was fivefold for Chinese (10.3% vs. 2.2%; p < 0.001), eightfold for Asian Indians (8.7% vs. 1.1%; p < 0.001), and twofold for Filipinos (16.8% vs. 9.0%). Moreover, 16.3% of US-born and 10.3% of foreign-born Filipinos were current smokers. Odds of ever using e-cigarettes, cigars, smokeless tobacco, and pipes in comparison to NHWs were lowest for Chinese (ORs 0.6, 0.5, 0.2, and 0.5). Discussion Filipinos had the highest current smoking rates of Asian ethnic groups. Though more Asian men were current smokers, the high rate of current smoking among Filipinas is concerning. More US-born Filipinos were current smokers than foreign-born, despite rates typically decreasing for US-born Asians. Investigating cultural factors contributing to less frequent use of tobacco products, such as alternative tobacco products among Chinese, may aid campaigns in curbing tobacco usage.